Contrastive Analysis of Discourse Representation In Indonesia Newspaper (KOMPAS) and English Newspaper Reports (Jakarta Post) - Syafryadin, Syafryadin (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Discourse representation deals with language structures which has crucial role not only for the text, but also for social practices. Newspaper is one of the real implementations of discourse representation because newspaper comprises several components in discourse representation. Newspaper in every country is made based on its language and every newspaper has difference and similarity in terms of discourse representation. Therefore, this study aimed to investigate the contrastive analysis of discourse representation in Indonesia newspaper and English newspaper reports. The subjects of this study were KOMPAS as representative of Indonesia newspaper and Jakarta Post as representative of English newspaper. This present study applied descriptive qualitative design which focused on representing verbs and modes of discourse representation (direct and indirect discourse). The findings of this study were that both newspapers have differences and similarities even though the difference was not quite dominant. The similarity of these newspapers could be seen from the use of reporting verbs and indirect discourse which were more dominant than the other parts in discourse representation. The difference could be seen also from representing verbs and modes of discourse representation. Although, reporting verbs are majority parts in Indonesia newspaper and English newspaper, but several words in Indonesia had the same translation into English. Manner of speaking verbs, mental verbs were still rare found in Indonesia newspaper. In Indonesia newspaper had only direct and indirect discourse, while in English newspaper had direct, indirect, free direct discourse, and indirect discourse in headline. In short, these newspapers have contrastive analysis in terms of discourse representation.